Evaluación de la reducción del tiempo de ciclo en cruces peatonales, ubicados entre dos intersecciones semaforizadas (2017)
Pedestrian crossings are implemented due to the need for people to cross avenues at different points along the way. Although most of these are implemented in corners, in many cases pedestrians require crossing in the middle of the block, increasing their exposure to accidents and injuries. Therefore, pedestrian crosses are the object of study of this research. The optimization of the traffic signals has focused mainly on minimizing the delays of the motorized modes, neglecting the travel times of the pedestrians. As a consequence, costs associated with walking increase in such a way that people choose to take motorized means to carry out the same travel. Mid-block crosses, although less frequent than crosses located on signalized intersections, are a frequent aspect of transport networks. The purpose of this research was to identify, in a pedestrian traffic light that is located in the middle of two traffic lights and with an equal cycle time, what effect will it have to reduce the cycle time at the pedestrian intersection in vehicular and pedestrian delays? As a result a matrix was obtained in which, for different vehicular and pedestrian volumes, the delays of each mode were evaluated equally, by means of the Total Average Delay (TAD) indicator. Through the study it was found that, under conditions of low vehicular flow, the delays associated with this mode are minimal. This can be used with a reduction of the traffic light cycle time of 60 seconds, which gives pedestrians the opportunity to cross the road in two opportunities, also reducing pedestrian delays. As vehicular volumes increase, the intersection traffic light should give a greater preference to the motorized means, increasing its green times and giving the pedestrians a single green time to cross the street.--Tomado del Formato de Documento de Grado.